Coronavirus Disease (COVID-19) Caused by (SARS-CoV-2) Infections: A Real Challenge for Human Gut Microbiota - Vodnar, Dan-Cristian; Mitrea, Laura; Teleky, Bernadette-Emoke; Szabo, Katalin; Călinoiu, Lavinia-Florina; Nemeş, Silvia-Amalia; Martău, Gheorghe-Adrian (Frontiers in Cellular and Infection Microbiology, 2020)
The current COVID-19 pandemic is a great challenge for worldwide researchers in the human microbiota area because the mechanisms and long-term effects of the infection at the GI level are not yet deeply understood. In the current review, scientific literature including original research articles, clinical studies, epidemiological reports, and review-type articles concerning human intestinal infection with SARS-CoV-2 and the possible consequences on the microbiota were reviewed. Moreover, the following aspects pertaining to COVID-19 have also been discussed: transmission, resistance in the human body, the impact of nutritional status in relation to the intestinal microbiota, and the impact of comorbid metabolic disorders such as inflammatory bowel disease (IBS), obesity, and type two diabetes (T2D). The articles investigated show that health, age, and nutritional status are associated with specific communities of bacterial species in the gut, which could influence the clinical course of COVID-19 infection. Fecal microbiota alterations were associated with fecal concentrations of SARS-CoV-2 and COVID-19 severity. Patients suffering from metabolic and gastrointestinal (GI) disorders are thought to be at a moderate-to-high risk of infection with SARS-CoV-2, indicating the direct implication of gut dysbiosis in COVID-19 severity. However, additional efforts are required to identify the initial GI symptoms of COVID-19 for possible early intervention.